Advances in the investigation of chronic non-communicable diseases in Peru - Del Castillo-Fernández, Darwin (2021)
Noncommunicable diseases (NCDs) are a major cause of disease burden in Peru as well as in other developing countries. Responses to control NCDs require multidisciplinary research, both locally and internationally. The CRONICAS Center of Excellence in Chronic Diseases at Universidad Peruana Cayetano Heredia, in Peru, has conducted scientific research in the field of NCDs in Peru for more than 10 years. This article highlights some of the scientific research, including epidemiological studies such as the PERU MIGRANT study, and the CRONICAS cohort study. We also summarize our results from systematic reviews in the field of NCDs and results of interventions to tackle NCDs. The scientific research studies conducted by CRONICAS signal potential advancements to counter NCDs in developing countries.